PENGARUH MEDIA PEMBELAJARAN MYSTERY BOX TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 2 NATAR LAMPUNG SELATAN - Dasa Noer Kharisma; Baharudin, Ayu Reza Ningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Mystery Box learning media is a proven solution that can improve students' understanding of the IPAS curriculum. This media is designed to improve cognitive understanding in more complex IPAS classes. In the digital age, the use of various forms of educational media has become increasingly common in various fields of life, including education. The purpose of this study was to determine whether the Mystery Box learning media could improve the social studies learning outcomes of fourth-grade students at SDN 2 Natar Lampung Selatan. This study is quantitative research. The design used is a quasi-experimental design (post-test only control design), which was conducted at SDN 2 Natar. This study used two groups, namely IV-A as the experimental group consisting of 26 students and IV-B as the control group consisting of 26 students, as well as one additional class as a validation class. The instruments used in this study included tests. Data analysis was performed using the t-test. Data were obtained from the post-test results. Analysis of the research results showed that the normality test produced values of 0.076 and 0.010, which means > 0.05, indicating that the data were normally distributed. The homogeneity test showed a value of 0.711 > 0.05, indicating that the data were homogeneous. The results of the hypothesis test using the independent sample t-test produced a value of 0.000 < 0.05, which means Ho is rejected and Ha is accepted, so it can be concluded that